2020
DOI: 10.1016/j.psj.2020.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization and the relationship between the reaction degree and the antioxidant activity of Maillard reaction products of chicken liver protein hydrolysates

Abstract: The aim of this study was to optimize the protein hydrolysates from chicken liver with xylose under Maillard reaction ( MR ) conditions using response surface methodology. The correlation between the browning degree, grafting degree, and the antioxidant activities of the Maillard reaction products ( MRPs ) was investigated. The optimal reaction conditions were achieved with a reaction temperature of 138.78°C, an initial pH of 7.99, and a reaction time of 93.14 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In addition, it has been shown that MRPs have remarkable antioxidant potential (Han et al, 2018). One previous study have shown that the antioxidant activity of MRPs which molecular weight is less than 1 kDa is about eight times to that of MRPs with molecular weight greater than 50 kDa ( Xiong et al,2020 ). Development of these nutritional and functional foods faces a huge challenge in demonstrating the efficacy of their biologically active ingredients in the body.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it has been shown that MRPs have remarkable antioxidant potential (Han et al, 2018). One previous study have shown that the antioxidant activity of MRPs which molecular weight is less than 1 kDa is about eight times to that of MRPs with molecular weight greater than 50 kDa ( Xiong et al,2020 ). Development of these nutritional and functional foods faces a huge challenge in demonstrating the efficacy of their biologically active ingredients in the body.…”
Section: Introductionmentioning
confidence: 98%
“…Chicken liver could be used as the additives for infant foods (Mart ınez et al 2006), or as ingredient for chicken liver paste products. Chicken liver also could be a resource to produce the food of pet (Xiong et al 2020). Furthermore, there are high content (above 20%) and good quality proteins in chicken liver.…”
Section: Introductionmentioning
confidence: 99%
“…1a,b). The glycated peptides were reported to have higher antioxidant activities than the non‐glycated ones (Xiong et al ., 2020). Similarly, Liu et al ., (2014) suggested that MR might be a promising mean for antioxidant activity enhancement in soy protein hydrolysates and whey protein isolate, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were claimed to influence the development of some diseases such as cancers (Beland et al ., 2013) and inflammatory diseases (ALjahdali & Carbonero, 2019), when the factors such as reaction time and temperature were not well managed. Nowadays, MR between protein hydrolysates/peptides and reducing sugars have gained much interest based on satisfactory functionalities as well as aroma and sensory attributes of the final products (K. Chen et al ., 2019; Xiong et al ., 2020; X. Zhang et al ., 2020). MRP prepared from chitoologosacharides‐lysine MR model presented potential antioxidant properties (Yu et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%